2019
DOI: 10.1109/access.2019.2924510
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and Ray Tracing Simulations for Non-Line-of-Sight Millimeter-Wave Channels in a Confined Corridor Environment

Abstract: This paper presents the radio propagation measurement, simulation, and analytical results in the 41-GHz millimeter-wave band for non-line-of-sight scenarios in a confined in-building corridor environment. High gain directional antennas are used at both the transmitter and receiver to realize longdistance transmission. Directional channel characteristics of the 41-GHz band, including the path loss model, the root-mean-square delay spread, the multipath statistics, the small scale fading characteristics, the pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Reference [16] investigated large scale fading characteristics such as path loss exponent (PLE), cross-polarization discrimination ratio (XPD), and shadowing factor at 45 GHz in three typical indoor environments. The non-line-of-sight (NLOS) channels in a confined in-building corridor in 41 GHz band were measured in [17]. In [18], the multipath dispersion characteristics of outdoor-to-indoor (O2I) propagation were presented in the angular and delay domains at 32 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [16] investigated large scale fading characteristics such as path loss exponent (PLE), cross-polarization discrimination ratio (XPD), and shadowing factor at 45 GHz in three typical indoor environments. The non-line-of-sight (NLOS) channels in a confined in-building corridor in 41 GHz band were measured in [17]. In [18], the multipath dispersion characteristics of outdoor-to-indoor (O2I) propagation were presented in the angular and delay domains at 32 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…The radio wave coverage in the tunnel environment has been studied for a long time [1][2][3] , and it can be modeled and predicted by measurements or by physics-based methods. Several measurement works on radio wave coverage in confined spaces have been published [4][5][6] . In [5], the radio wave transmission in the millimeter-wave band of 41 GHz for non-line-of-sight scenarios in a confined building corridor environment is measured.…”
Section: Introductionmentioning
confidence: 99%
“…Several measurement works on radio wave coverage in confined spaces have been published [4][5][6] . In [5], the radio wave transmission in the millimeter-wave band of 41 GHz for non-line-of-sight scenarios in a confined building corridor environment is measured. The channel characteristics, including the path loss model, root-mean-square delay spread, multipath statistics, small-scale fading characteristics, power delay profile, and power levels received from different antenna locations, are analyzed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The modified-CI model offered the same PLE as FI model with less computational complexity. In [103], the propagation characteristic in a confined corridor with a corner was investigated with highly directional antennas at 41 GHz. The result from the study showed that the angle of the corridor corner can result in power loss.…”
Section: Indoor Room Hall and Hallway/corridormentioning
confidence: 99%